Prevalence and Correlates of Dental Fear, Pain, and Cariesin Libyan Children and Adolescents: A Cross-Sectional Studyin Three Northeastern Citie - BENTAHER, HIATHAM; AYOUB, GIUMA (Sharwes Scientific Journal, 2025)
Dental fear and anxiety (DFA) remain significant barriers to timely and effective oral healthcare for children and adolescents, frequently leading to avoidance behaviours and increased risk of untreated dental conditions. While global evidence highlights the prevalence and consequences of DFA, populations in North Africa particularly in Libya are underrepresented in epidemiological data. This cross-sectional study examined the prevalence of DFA, dental pain, and caries, and their associations with sociodemographic, behavioural, and clinical variables among 1,800 children and adolescents aged 6 to 17 years attending public clinics in Al Bayda, Derna, and Tobruk. Data were collected through five structured tools: the Sociodemographic and Behavioural Profile Scale (SDBPS), Dental Pain and Discomfort Scale (DPDS), Children’s Fear Survey Schedule–Dental Subscale (CFSS-DS), SelfReported Caries History Scale (SRCHS), and Clinical Examination Record (CER). Analysis revealed that younger age and female gender were significantly associated with higher DFA scores (p < 0.001). Recent dental pain strongly predicted elevated anxiety levels (β = 0.34, p < 0.001), while irregular brushing and lack of prior dental visits correlated with both higher DFA and greater caries prevalence (OR = 2.32, p < 0.001). Lower maternal employment was also associated with increased risk of caries and DFA (OR = 1.87, p = 0.004). The findings suggest that emotional distress and clinical burden are jointly influenced by behavioural routines and structural disadvantage. These results highlight the need for integrated, age-appropriate, and socially responsive oral health strategies that simultaneously address psychological barriers and promote equitable access to preventive care for children in underserved Libyan regions.